2022
DOI: 10.1038/s41538-022-00136-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumer purchase intention towards a quick response (QR) code for antibiotic information: an exploratory study

Abstract: Increasing awareness of antimicrobial resistance (AMR) has raised concerns surrounding antimicrobial use (AMU) in food-producing animals and has focused attention towards livestock production free from antibiotic use. As antibiotic-free livestock production proliferates in the UK, there is an increasing need to implement a system, such as the use of a QR code, to provide consumers with reliable antibiotic information while ensuring that animal welfare standards are upheld. Subsequently, this study aims to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Intention to buy meat produced without the preventive use of antibiotics was measured by asking participants to indicate their degree of agreement with two statements adapted from Bradford et al [ 54 ]: “I intend to buy meat produced without the preventive use of antibiotics” and “I will look for meat produced without the preventive use of antibiotics” ( α = 0.75).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intention to buy meat produced without the preventive use of antibiotics was measured by asking participants to indicate their degree of agreement with two statements adapted from Bradford et al [ 54 ]: “I intend to buy meat produced without the preventive use of antibiotics” and “I will look for meat produced without the preventive use of antibiotics” ( α = 0.75).…”
Section: Methodsmentioning
confidence: 99%
“…Research so far has mainly focused on investigating consumers’ knowledge about, perceptions of, and attitudes towards the overall use of antibiotics in food animals [ 54 65 ]. The results of these studies suggested that, although having little knowledge about antibiotic use in food animals and its contribution to antibiotic resistance, consumers somehow believed antibiotics are widely used in livestock industries and concerned about it [ 54 60 , 62 , 63 ]. Moreover, the public concern about overall antibiotic use in food animals has facilitated the purchase demand and higher willingness to pay for animal-derived food produced without any use of antibiotics [ 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the absolute WTPs for the traceability QR code and PDO labels were nearly similar. However, besides providing only the locality and traditionality of the products, embedding traceability information in QR codes has more advantages than PDO labelling as it can help to convey more direct information to consumers such as information regarding antibiotic use (Bradford et al, 2022), free of child labour (Lafargue et al, 2022) and other sustainability claims (Bashir, 2022). Furthermore, consumers' awareness and knowledge of the certification schemes can be limited as proven in the case of PDO in several countries (Grunert and Aachmann, 2016).…”
Section: Bivariate Correlations With Consumer Ethnocentrismmentioning
confidence: 99%
“…The adoption of QR codes on food packaging has been studied using the Theory of Planned Behaviour (Bradford et al ., 2022; Ozkaya et al ., 2015) and Technological Acceptance Modelling (Kim and Woo, 2016), which have primarily focussed on explaining the intention to adopt QR codes. Kim and Woo (2016) demonstrated that consumers are more willing to scan a QR code on food packaging if they perceive the embedded information to be informative and helpful in their purchase decisions.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…QR codes serve as a link between physical products and digital information, and are deemed advantageous tools for augmenting consumer empowerment. Consumers promptly access a wealth of information through a smartphone scan of QR codes, which enables them to evaluate the authenticity and safety of a product [68][69][70][71].…”
Section: Qr Codes-based Intelligent Biosensorsmentioning
confidence: 99%